Interpolation sural flap in acute trauma patients - Tapan, Mehmet; Şeker, Yunus Emre; Zöhre, Taylan Cihan; Korkut, Ali Emre; Özkan, Özlenen; Özkan, Ömer (The European Research Journal, 2023)
Objectives: Distal lower leg wounds, regardless of cause, and acute trauma wounds, regardless of site, are difficult. Reconstruction of both situations are much more challenging. Interpolation sural flap is a good alternative for this type of reconstruction. Methods: Fourteen interpolation sural flap were harvested to reconstruct for distal leg region wounds due to acute trauma. Ten male and four female patients aged from 10 to 59 years old were included this study. Results: All flaps survived. No venous congestion and total flap necrosis was seen. There were 4 complications, and all of them were corrected with short interventions. After second stage, no complication was seen. Conclusions: Interpolation sural flap modification has many advantages including reliability, no venous congestion, immediate reconstruction without a surgical team. However, it is a two-staged reconstruction and its donor site scarring can be serious.